Improving Student Learning Outcomes in Science: A Culturally Responsive Approach Using Problem-Based Learning - Sofiya, Rizka; Hikmawati, Hikmawati; Zohriana, Zohriana (Pascasarjana, Mataram University, 2025)
This study aimed to improve student learning outcomes through the Problem-Based Learning (PBL) model combined with the Culturally Responsive Teaching (CRT) approach. The research focused on teaching the concept of metamorphosis in animals using the local folklore,